THE EXPERIENCE OF USING FILIAL PLAY THERAPY FROM THE PERSPECTIVE OF ADOPTIVE PARENTS: A CASE STUDY OF FAMILY ADJUSTMENT - Chizk, Georgeanna (East Carolina University, 2018)
Adoption can consist of both positive experiences as well as challenges in parent-child relationship development. Research suggests that filial play therapy is helpful in fostering a secure attachment relationship. Given its potential role in establishing a parent-child bond, filial play therapy may an option for adoptive parents in building meaningful connection and a secure parent-child attachment relationship. The purpose of this study was to explore adoptive parents' experiences with using post-adoption filial play therapy in an effort to investigate the perceived usefulness of filial play therapy in improving attachment relationships between parent and child. Mixed-methods multiple case study methodology of three cases was used to explore adoptive parents' experiences with and perceptions about filial play therapy. Cross-case analysis revealed that adoptive families' experiences were highly complex. Parents had positive experiences using filial play therapy with their child and reported the development of emotional connection and a decrease frequency of adverse child behaviors. Given the positive outcomes of using filial play therapy in the adoption experience, parents suggested that more mental health providers be trained in filial play therapy to meet parent-child relationship needs within adoptive families.
Keywords: case study; family adjustment; Adoptive parents; Parent and child; Play therapy; Attachment behavior in children